1977
DOI: 10.1002/bjs.1800640302
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy: Extent of resection and late results

Abstract: Opinion is divided as to the necessary extent of parathyroid resection in primary hyperparathyroidism. Some surgeons urge that subtotal parathyroidectomy be performed routinely, while others reserve subtotal resections for patients with parathyroid hyperplasia. In a review of 102 patients treated by parathyroidectomy for primary hyperparathyroidism and subsequently followed up for an average of 6 years, there were 73 patients with parathyroid adenoma, 26 with hyperplasia and 3 with carcinoma. The adenoma was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…: personal communication). These data have been confirmed by Cooke et al [3] and by van Heerden et al [4] who reported single adenomas in 89% of 207 patients treated at the Mayo Clinic between 1967 and 1970. Further, these authors [4] quoted the study by Parnell, Scholz, and Beahrs which showed in a 1-8 year follow-up a diagnostic error rate of less than a 1% as revealed by recurrence of the hypercalcemia (presumably due to parathyroid hyperplasia).…”
Section: Department Of Pathology University Of Arkansas College Of Me...supporting
confidence: 56%
“…: personal communication). These data have been confirmed by Cooke et al [3] and by van Heerden et al [4] who reported single adenomas in 89% of 207 patients treated at the Mayo Clinic between 1967 and 1970. Further, these authors [4] quoted the study by Parnell, Scholz, and Beahrs which showed in a 1-8 year follow-up a diagnostic error rate of less than a 1% as revealed by recurrence of the hypercalcemia (presumably due to parathyroid hyperplasia).…”
Section: Department Of Pathology University Of Arkansas College Of Me...supporting
confidence: 56%
“…Bilateral and unilateral surgical approaches have been advocated. Some surgeons Use the histological appearance of parathyroid tissue at frozen section to determine the extent of parathyroidectomy [1][2][3]. When a hyperplastic parathyroid gland is reported by the Pathologist, 3 or 31/2 parathyroids are removed.…”
mentioning
confidence: 99%
“…The majority of large series of patients with primary hyperparathyroidism have been reported from major teaching centres 1 , 2 , 3 , 4 , 5 . In Great Britain, studies have also been reported from major cities 6 , 7 or metropolitan areas 8 , following mass biochemical screening programmes or the collection of data from major hospitals within an area, but few studies have been reported from peripheral units 9 or clinics.…”
Section: Introductionmentioning
confidence: 99%